Digital Culture & Society (DCS) : Vol. 4, Issue 1/2018 – Rethinking AI: Neural Networks, Biometrics and the New Artificial Intelligence /: Vol. 4, Issue 1/2018 – Rethinking AI: Neural Networks, Biometrics and the New Artificial Intelligence. (2018) - Unknown
No abstract available